MARKETING MIX STRATEGY ANALYSIS OF WARDAH PRODUCT PURCHASE DECISIONS (CASE STUDY IN PEKANBARU) - Wibowo, Yudho; Arsyelan, Fajrig (International Journal of Business and Information Technology, 2021)
This study aims to analyze the effect of marketing mix variables consisting of product (X 1 ), price (X 2 ), place/distribution channel (X 3 ) and promotion (X 4 ) on purchasing decisions (Y ) for Wardah products in Pekanbaru. This research was conducted at outlets that market Wardah products in Pekanbaru city with a total sample of 99 outlets studied with cluster sampling methode. The analysis showed that the variables of the marketing mix consisting of product ( X 1 ), price ( X 2 ), place / distribution channels ( X 3 ) and promotion ( X 4 ) are partial and simultaneously have a significant influence on product purchasing decisions Wardah in Pekanbaru. The value of the correlation coefficient (R) = 0.481 which means that the dependent variable and the independent variable have a moderate relationship. The coefficient of determination amounting to 0 .231 which means that the variables of the marketing mix contributed 23.1 % to the purchase decision.